Institutional Communication in the tourism sector in crisis: a strategy of Destination Management Organization (DMO) to counter oil slicks as electoral strategy - Rodríguez-Toubes Muñiz, Diego (2022)
Tourism destinations need to manage crises and disasters caused by events that affect the image of the destination. Effective communication is essential in these situations. Destination Management Organizations, DMO, are the appropriate entities to lead the communication process before, during and after the crisis in order to achieve a quick recovery in tourism. A research into the DMO crisis communication in Galicia, Spain, to cope with the oil slick may provide a better understanding about how to manage crisis communication in these situations.